FAKTOR – FAKTOR YANG MEMPENGARUHI PENGHIMPUNAN DEPOSITO MUDHARABAH PADA BANK PEMBIAYAAN RAKYAT SYARI’AH DI INDONESIA PERIODE 2012-2014 - Ai Fitri Islami (UIN Siber Syekh Nurjati Cirebon, 2018)
ABSTRACT The purpose of this study was to determine the long-term equilibrium and the influence of institutional and macro-economic variables of the accumulation of mudharaba time deposits on Sharia Financing Bank in Indonesia at 2012.1 to 2014.12. This study uses Partial Adjustment Model regression analysis to estimate the effect of independent variables on the dependent variable in the short term and long term. Research variables consisted of gathering deposits mudaraba, GDP, BI Rate, Inflation, profit sharing ratio, number of offices, number of employees, and promotion costs.The study concluded there is a balance of long-term institutional and macro-economic variables of the accumulation of mudharaba time deposits in Sharia Financing Bank in Indonesia. Institutional variables partially significant effect on the accumulation of mudharaba time deposits only revenue sharing in both short and long term. Macroeconomic variables partially significant effect on the accumulation of mudharaba time deposits in Indonesia is only BI Rate in short term and long term. Institutional and macroeconomic variables simultaneously significantly affect the accumulation of mudharaba time deposit deposits. In the short term profit sharing ratio coefficient greater than BI Rate, thus summed variable profit sharing ratio is more influential than the BI Rate. In the long term variable BI Rate is more influential than the profit sharing ratio. Keywords: deposits mudaraba, GDP, BI Rate, Inflation, profit sharing ratio, number of offices, number of employees, and promotion costs. ABSTRAK Tujuan penelitian ini adalah untuk mengetahui keseimbangan jangka panjang dan pengaruh variabel kelembagaan dan makro ekonomi terhadap penghimpunan deposito mudharabah Bank Pembiayaan Rakyat Syari’ah (BPRS) di Indonesia periode 2012.1 s.d. 2014.12. Penelitian ini menggunakan metode analisis regresi Partial Adjustment Model untuk mengestimasi pengaruh variabel bebas terhadap variabel tidak bebas dalam jangka pendek dan jangka panjang.Variabel-variabel penelitian terdiri daripenghimpunan deposito mudharabah, GDP, BI Rate, Inflasi, nisbah bagi hasil, jumlah kantor, jumlah karyawan, dan biaya promosi.Penelitian menyimpulkan terdapat keseimbangan jangka panjang variabel kelembagaan dan makro ekonomi terhadap penghimpunan deposito mudharabah BPRS di Indonesia. Variabel kelembagaan yang berpengaruh nyata secara parsial terhadap penghimpunan deposito mudharabahhanya nisbah bagi hasil baik dalam jangka pendek dan jangka panjang. Variabel makroekonomi yang berpengaruh nyata secara parsial terhadap penghimpunan deposito mudharabah hanya BI Rate baik dalam jangka pendek dan jangka panjang. Variabel kelembagaan dan makroekonomi secara serempak berpengaruh nyata terhadap penghimpunan deposito mudharabah. Dalam jangka pendek koefisien nisbah bagi hasil lebih besar daripada BI Rate, sehingga disimpulkan variabel nisbah bagi hasil lebih berpengaruh daripada BI Rate. Dalam jangka panjang variabel BI Rate lebih berpengaruh daripada nisbah bagi hasil. Kata kunci: deposito mudharabah, GDP, BI Rate, Inflasi, nisbah bagi hasil, jumlah kantor, jumlah karyawan, dan biaya promosi.